Comparison of winding configurations in double‐stator switched reluctance machines. Issue 8 (11th August 2017) - Cosoroaba, Eva; Bostanci, Emine; Li, Yinan; Wang, Wei; Fahimi, Babak
Abstract : The double‐stator configuration of the switched reluctance machine (SRM) aims to maximise the energy conversion efficiency by optimising the ratio of motional force to the total magnetic force. Maintaining the attractive features of SRM, the double‐stator switched reluctance machine (DSSRM) proves to have higher torque/power density than the conventional SRM, which is a crucial feature for traction applications. The original winding configuration used in DSSRM is the full‐pitch winding, which yields high‐power density but causes significant heat within the machine's end windings. As end windings do not take part in torque generation, concentrated windings were proposed to reduce the heat as well as to reduce the size, cost, and weight of the machine. This study provides a detailed comparative analysis of the effects that the winding configuration has on the performance of a 100kW DSSRM, with emphasis on flux density distribution, efficiency, and heat generation. It is concluded that the concentrated windings are a better alternative to the full‐pitch windings in DSSRM.